2010
DOI: 10.1101/gr.100594.109
|View full text |Cite
|
Sign up to set email alerts
|

Rewirable gene regulatory networks in the preimplantation embryonic development of three mammalian species

Abstract: Mammalian preimplantation embryonic development (PED) is thought to be governed by highly conserved processes. While it had been suggested that some plasticity of conserved signaling networks exists among different mammalian species, it was not known to what extent modulation of the genomes and the regulatory proteins could “rewire” the gene regulatory networks (GRN) that control PED. We therefore generated global transcriptional profiles from three mammalian species (human, mouse, and bovine) at representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
224
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(243 citation statements)
references
References 42 publications
15
224
3
1
Order By: Relevance
“…Research in the mouse and other mammals has identified the main factors and signals involved in embryonic pluripotency, but we still have little insight into how deeply conserved the EP-GRN is and how it appeared during evolution. Recent studies in nonmammalian vertebrates argue for conservation of pluripotency and its genetic control (6, 7), whereas comparative genome-wide studies be- tween different mammals point to a high degree of plasticity of the EP-GRN (37,38). Our results comparing mouse and chick help clarify this apparent contradiction, because they show that, although core pluripotency factors are present in other vertebrates, the way they are connected in the EP-GRN is unique to mammals.…”
Section: Discussionmentioning
confidence: 41%
“…Research in the mouse and other mammals has identified the main factors and signals involved in embryonic pluripotency, but we still have little insight into how deeply conserved the EP-GRN is and how it appeared during evolution. Recent studies in nonmammalian vertebrates argue for conservation of pluripotency and its genetic control (6, 7), whereas comparative genome-wide studies be- tween different mammals point to a high degree of plasticity of the EP-GRN (37,38). Our results comparing mouse and chick help clarify this apparent contradiction, because they show that, although core pluripotency factors are present in other vertebrates, the way they are connected in the EP-GRN is unique to mammals.…”
Section: Discussionmentioning
confidence: 41%
“…For each observed outcome, the relative contributions of oxi-mC production and DNA demethylation may be distinguished by comparing cells deficient in DNA methyltransferases, which would be depleted for both 5mC and oxi-mC, with cells deficient in TET proteins, which lack only oxi-mC. Specific downstream mechanisms include altered recruitment of key transcription factors to their binding sites in DNA, either through direct modification of the binding sequences, modulation of chromatin accessibility, or both; retrotransposon modification and expression, because insertion of these elements is known to create alternative promoters for host genes during early embryogenesis (70,71); and changes in local histone modifications, as suggested by an early study in which DNA methylation in the gene body was shown to regulate Pol II elongation efficiency through H3K4-di/tri methylation and H3K9/14 acetylation (72). Future studies will clarify these points.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-species microarray hybridisation study revealed that gene expression profiles in bovine and human blastocysts were to a large extent identical (Adjaye et al 2007). Similarly, the transcription profiles during maternal-zygotic transition are similar between the two species (Xie et al 2010). Furthermore, the amino acid sequence of bovine IGF1 is identical to that of human IGF1 (Honegger & Humbel 1986, Francis et al 1988.…”
Section: Introductionmentioning
confidence: 99%